Evaluation of the Linear Relationship Between Pulse Arrival Time and Blood Pressure in ICU Patients: Potential and Limitations - Escobar-Restrepo, Braiam; Torres-Villa, Robinson; Kyriacou, Panayiotis A. (Frontiers in Physiology, 2018)
A variety of techniques based on the indirect measurement of blood pressure by Pulse Transit Time (PTT) have been explored over the past few years. Such an approach have the potential in providing continuous and non-invasive beat to beat blood pressure without the use of a cuff. Pulse Arrival Time (PAT) which includes the cardiac pre-ejection period has been proposed as a surrogate of PTT, however the balance between its questioned accuracy and measurement simplicity has yet to be established. The present work assessed the degree of linear relationship between PAT and blood pressure on 96 hours of continuous electrocardiography and invasive radial blood pressure waveforms in a group of eleven ICU patients. The overall Pearson correlation coefficient for systolic and diastolic blood pressure was -0.5 and -0.42 respectively, while the mean absolute error was 4 and 7.8 mmHg. It was concluded that the utilisation of PAT for the continuous non-invasive blood pressure estimation is rather limited according to the experimental setup, nonetheless the correlation coefficient performed better when the range of variation of blood pressure was high over periods of 30 min suggesting that PAT has the potential to be used as indicator of changes relating to hypertensive or hypotensive episodes